Deteksi Penyakit Tanaman Cabai Rawit (Capsicum frutescens L.) yang Tumbuh Disekitar Tanaman Jeruk Bergejala Citrus Vein Phloem Degeneration (CVPD) Menggunakan Teknik Polymerase Chain Reaction (PCR) - PASARI, NI KADEK DWI; WIRAWAN, I GEDE PUTU; SRITAMIN, MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.7, No.1, Januari 2018, 2018)
Detection of Chilli plant (Capsicum frutescens L.) which Grow in the Area of Citrus Cultivation that had symptoms of Citrus Vein Phloem Degeneration (CVPD) Using Polymerase Chain Reaction (PCR) Technique Liberibacter bacteria live and thrive inside the phloem tissue CVPD affected plants, the bacteria exhibit a progressive degeneration of the phloem tissue that inhibit phloem nutrient transport through the entire plan.. As the attack of Liberibacterasiaticus cause Citrus Vein Phloem Degeneration (CVPD) disease in citrus plant, it is necessary to do research on the chilli plant around citrus plant area to know whether bacteria of Liberibacter also attack the chilli plant by using PCR.The results of this study indicate that the chilli plants with CVPD symptoms which are suspected to be caused by the bacterium Liberibacter by usingLiberibacter asiaticus primer and Liberibacter solanaceae which is them specific primer of 16S rDNA are not proven. The result showed chilli plants with similar symptom to CVPD in Mangguh village, Kintamani sub-district were not to be caused by Liberibacter asiaticus and Liberibactersolanaceae.